Lack of significant seasonal association between serum 25(OH)D concentration, muscle mass and strength in postmenopausal women from the D-FINES longitudinal study. (13th December 2022) - Welford, Anneka E.; Darling, Andrea L.; Allison, Sarah J.; Lanham-New, Susan A.; Greig, Carolyn A.
Abstract: The aim of the present study was to assess the seasonal relationship between serum 25(OH)D concentration, lean mass and muscle strength. This was a secondary data analysis of a subgroup of 102 postmenopausal women participating in the 2006–2007 D-FINES (Vitamin D, Food Intake, Nutrition and Exposure to Sunlight in Southern England) study. The cohort was assessed as two age subgroups: <65 years ( n =80) and ≥65 years ( n =22). Outcome measures included lean mass (DXA), muscle strength (handgrip dynamometry) and serum 25(OH)D concentration (enzymeimmunoassay). Derived outcomes included appendicular skeletal muscle mass (ASM) and relative appendicular skeletal muscle index (RASM). Sarcopenia status was assessed using the European Working Group on Sarcopenia in Older People 2018 criteria. Non-parametric partial correlation using BMI as a covariate was used to evaluate the study aims. There were no statistically significant associations between total lean mass, ASM or RASM and 25(OH)D in any group at any season. There was a trend for handgrip strength to be positively associated with serum 25(OH)D concentration. There was a trend showing a higher prevalence of sarcopenia in women ≥65 years. Sarcopenia status appeared transient for five women. In conclusion, the present study found no significant association between vitamin D status and functional indicators of musculoskeletal health, which were additionally not affected by season.